Field efficacy of granular formulations of bacillus thuringiensis israelensis: strain Am65-52 against floodwater mosquitoes in Poland and Germany - Rydzanicz, Katarzyna; DeChant, Peter; Becker, Norbert (Journal of the American Mosquito Control Association, 2010)
This paper presents results of studies evaluating the efficacy of various granular formulations of VectoBac® (Bacillus thuringiensis israelensis de Barjac [Bti] H-14 strain AM65-52) against immature mosquitoes in 2 distinct habitats in Poland and Germany. Meadows intermittently flooded with sewage water in the city of Wroclaw, Poland, provide ideal habitats for immature stages of Aedes caspius, Ae. vexans, and Culex pipiens pipiens. Helicopter applications of VectoBac G and VectoBac TP sand granules (VectoBac TP-SG) at rates of 5 and 10 kg/ha to the meadows resulted in between 70.9% and 97.4% larval mortality. In Germany, some swampy woodlands in the upper Rhine Valley provide ideal habitats for snowmelt mosquitoes, Aedes cantans, Ae. punctor, Ae. rusticus, and Ae. communis. Ground applications of VectoBac G, VectoBac TP-SG, and VectoBac WG IcyPearls (VectoBac WG-IP) were made to these habitats when the water temperature was ∼7°C. Larval mortality at 7-day post-application ranged from 90.9% (VectoBac TP-SG: 10 kg/ha) to 98.0% (VectoBac WG-IP: 15 kg/ha). In a separate microcosm trial within the same habitat, all 3 granule formulations controlled larvae of Ae. cantans for 3 wk.